Aplicativo para dispositivo móvel android para suporte ao processo de inventariamento de estoque - Costa, Danilo David Pereira (2015)
The propose of this project, is to develop a app to mobile device to help in the data collect to the inventory of products process to the company Dream System's customers. The customers of the Dream Systems company act in the pharmaceutical industry and to check their inventory, they need of a practice tool to this process. In the base of the identification of products through code bar, it was studied the possibility do capture the image of this code, and read it through the android app to mobile device. To reach this objective, was utilized the Zxing lib that through the camera of the mobile phone, it capture the code bar image and return the code of the image. Through of the capture and the reading of the code through of the mobile phone, the customers will identify your products and quantities, it will be stored and process this data to help in the periodic check of their inventory.